THE IMPACT OF MOTIVATIONS BEHIND MALAYSIA’S ENERGY INITIATIVES (Journal of Governance and Development (JGD), 2022)
This research examines Malaysia’s involvement in activities which render energy as the subject and/or object of foreign policies, either via bilateral or multilateral engagements, from the perspective of Neoliberal Institutionalism. Malaysia’s increased involvement in theglobal energy market necessitates this research which seeks to determine the significance of energy in Malaysia’s economy anddiplomacy, to understand Malaysia's motivation for its involvement in these co-operations. For this research, information is obtained through various official sources, interviews, published statistical data and past studies. The research shows that energy contributes significantly to Malaysia’s economy. Malaysia’s involvement in Lao PDR-Thailand- Malaysia-Singapore Power Integration Project (LTMS-PIP) initiative demonstrates the viability of multilateral electricity trade in the region. The Four-Fuel Diversification Policy 1981 (4FDP 1981) which increases natural gas utilization and the construction of the Peninsula Gas Utilisation (PGU) pipeline in Peninsular Malaysia are related to Malaysia’s involvement in Malaysia-Thailand Joint Development Area (MT-JDA), whereas these initiatives contribute towards enhancing Malaysia’s energy security, Malaysia can still play proactive roles in regional energy cooperation, as regional energy hub or transit state. Malaysia might also want to consider consolidating its energy administration for efficiency. Malaysia’s experience in negotiating for JDA is also useful in addressing the current disputes in South China Sea.